University Graduates and the Entrepreneurial Intention: Evidence from Indonesia - Axellina Muara Setyanti (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
Higher education institutions are expected to cope and respond to the dynamic of society, participate in job creation and generate economic productivity. One way to make it happen is through entrepreneurship. This research aimed to propose an entrepreneurial intention model specific for higher education graduates in Indonesia. Using data from Survei Angkatan Kerja Nasional (Sakernas) 2019 and Probit analysis, this study found that there was a declining intention in graduates with higher education. So does the graduates with training certificate tend to have a lower intention. These implied that higher human capital, which is formed from education and training, tends to lead higher education graduates to non-entrepreneurship occupations. However, there is an increasing trend in entrepreneurial intention for both fresh graduates and those who have had previous jobs. Men in more mature age have higher intention into entrepreneurship, but after certain age there is an inverted U-shape relation between graduates’ age and their entrepreneurial intention.